2016
DOI: 10.1149/2.0621608jes
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Considerations for Improving the Pulse Power of a Battery through the Addition of a Second Electrochemically Active Material

Abstract: Porous electrode theory is used to conduct case studies for when the addition of a second electrochemically active material can improve the pulse-power performance of an electrode. Case studies are conducted for the positive electrode of a sodium metal-halide battery and the graphite negative electrode of a lithium "rocking chair" battery. The replacement of a fraction of the nickel chloride capacity with iron chloride in a sodium metal-halide electrode and the replacement of a fraction of the graphite capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Silver plays an interesting covalent structural role in the α-MnO 2 framework, with decreasing tunnel size upon increasing silver ( x ) content . The reduction displacement mechanism of Ag + serves as an interesting mode to increase cathode electrical transport in situ; as example, the electrically insulating Ag 2 VO 2 PO 4 cathode , reduces to form a network of dispersed, conductive Ag 0 particles that support fast electron transport. , There have been previous attempts to apply the Ag + reduction displacement mechanism to silver hollandite. , However, the detectable formation of silver metal occurs at late stages of electrochemical lithiation (>0.5 electron equivalents (ee) per Mn formula unit, >4ee per Mn 8 O 16 formula unit) and moderate stages of electrochemical sodiation (<0.5ee/Mn) in nonaqueous electrolytes, and is electrochemically irreversible based on prior reports for Ag x Mn 8 O 16 . At low potentials, silver is known to undergo a size-dependent reversible electrochemical alloying process with lithium; , however, there are limited examples of reversible silver metal/silver ion electrochemistry at potentials suitable for a cathode material (i.e., >1.5 V versus lithium).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver plays an interesting covalent structural role in the α-MnO 2 framework, with decreasing tunnel size upon increasing silver ( x ) content . The reduction displacement mechanism of Ag + serves as an interesting mode to increase cathode electrical transport in situ; as example, the electrically insulating Ag 2 VO 2 PO 4 cathode , reduces to form a network of dispersed, conductive Ag 0 particles that support fast electron transport. , There have been previous attempts to apply the Ag + reduction displacement mechanism to silver hollandite. , However, the detectable formation of silver metal occurs at late stages of electrochemical lithiation (>0.5 electron equivalents (ee) per Mn formula unit, >4ee per Mn 8 O 16 formula unit) and moderate stages of electrochemical sodiation (<0.5ee/Mn) in nonaqueous electrolytes, and is electrochemically irreversible based on prior reports for Ag x Mn 8 O 16 . At low potentials, silver is known to undergo a size-dependent reversible electrochemical alloying process with lithium; , however, there are limited examples of reversible silver metal/silver ion electrochemistry at potentials suitable for a cathode material (i.e., >1.5 V versus lithium).…”
Section: Introductionmentioning
confidence: 99%
“…18 The reduction displacement mechanism of Ag + serves as an interesting mode to increase cathode electrical transport in situ; as example, the electrically insulating Ag 2 VO 2 PO 4 cathode 25,26 reduces to form a network of dispersed, conductive Ag 0 particles that support fast electron transport. 27,28 There have been previous attempts to apply the Ag + reduction displacement mechanism to silver hollandite. 24,29−35 However, the detectable formation of silver metal occurs at late stages of electrochemical lithiation (>0.5 electron equivalents (ee) per Mn formula unit, >4ee per Mn 8 O 16 formula unit) 18 and moderate stages of electrochemical sodiation (<0.5ee/Mn) 35 in nonaqueous electrolytes, and is electrochemically irreversible based on prior reports for Ag x Mn 8 O 16 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Towards this goal, the development of materials containing Ag + is pursued for fundamental interest because the reduced product can contain a network of atomically dispersed, conductive Ag 0 particles that support fast electron transport throughout the bulk. 1,2 Minute amounts of dispersed Ag + are known to signicantly improve electronic transport; as example, cathodes of the silver-vanadium-phosphate-oxide type show percolation thresholds with 0.3% volume reduction of Ag + concurrently resulting in 10 6 decrease in electrical resistance. [3][4][5] Silver vanadium oxide (SVO) cathodes remain the dominant material in implantable cardiac debrillator batteries due to this reductive displacement mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternate strategy, our group has demonstrated that electrical conductivity can be improved by taking advantage of reduction displacement mechanisms in silver-ion-containing materials. For example, the electrically insulating Ag 2 VO 2 PO 4 cathode reduces to form a network of dispersed, conductive Ag 0 particles that support fast electron transport. , This Ag 0 network provides advantages which carbon alone cannot attain, as the Ag + precursor is controlled and distributed on a smaller atomic length scale as part of the inherent crystal structure; that is, Ag 0 is generated with immediate proximity to each active material particle.…”
Section: Introductionmentioning
confidence: 99%